2020
DOI: 10.1111/andr.12836
|View full text |Cite
|
Sign up to set email alerts
|

Worse progression of COVID‐19 in men: Is testosterone a key factor?

Abstract: Background The novel severe acute respiratory syndrome coronavirus (SARS‐CoV‐2) disease 2019 (COVID‐19) seems to have a worse clinical course among infected men compared with women, thus highlighting concerns about gender predisposition to serious prognosis. Therefore, androgens, particularly testosterone (T), could be suspected as playing a critical role in driving this excess of risk. However, gonadal function in critically ill men is actually unknown, mainly because serum T concentration is not routinely me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(132 citation statements)
references
References 183 publications
(275 reference statements)
4
122
0
6
Order By: Relevance
“…The measurement of testosterone levels is not routinely undertaken and therefore there is little empirical evidence of its impact, with currently only one smallscale study of 31 patients demonstrating an increased risk [108]. Such that this link remains mostly a hypothesis based on the already recognized negative effect of low testosterone on recognized preexisting morbidity such as epithelial dysfunction and cardiovascular disease, the risk of obesity; and the metabolic syndrome [109,112,113114]. There may also be an association with the immune response to the virus, through an association with increased pro-inflammatory cytokines [115].…”
Section: Reproductive Healthmentioning
confidence: 99%
“…The measurement of testosterone levels is not routinely undertaken and therefore there is little empirical evidence of its impact, with currently only one smallscale study of 31 patients demonstrating an increased risk [108]. Such that this link remains mostly a hypothesis based on the already recognized negative effect of low testosterone on recognized preexisting morbidity such as epithelial dysfunction and cardiovascular disease, the risk of obesity; and the metabolic syndrome [109,112,113114]. There may also be an association with the immune response to the virus, through an association with increased pro-inflammatory cytokines [115].…”
Section: Reproductive Healthmentioning
confidence: 99%
“…2(c)], which is the only steroid for which a structure of a complex with albumin has been determined (Czub et al, 2019). Testosterone is suspected of playing a critical role in driving the pronounced excess of COVID-19 lethality in male patients (Pozzilli & Lenzi, 2020), and low testosterone levels predict adverse clinical outcomes (Giagulli et al, 2020). Critically ill male COVID-19 patients suffer from severe testosterone deficiency, which may or may not be caused by the disease.…”
Section: Competing Compounds and Albumin Glycation May Impair Dexametmentioning
confidence: 99%
“…For example, testosterone was top-ranked by XGboost, with higher levels associated with increased risk. Studies have suggested elevated or reduced testosterone levels may be both associated with a more severe clinical course 31 . Higher IGF-1 appeared to be associated with greater mortality in cohort B.…”
Section: Highlights Of Potential Risk Factorsmentioning
confidence: 99%